MENINGKATKAN PERKEMBANGAN MOTORIK HALUS ANAK MELALUI KEGIATAN MOZAIK DI PAUD HUBBUL ILMI - Atika Nur Fadhilah; Lydia Margaretha; Syisva Nurwita (Early Childhood Research and Practice, 2021)
This study aims to determine the improvement of children's fine motor skills through mosaic activities at PAUD Hubbul Ilmi in Sukamakmur Village of Girimulya Sub-District of North Bengkulu Regency. This research uses Classroom Action Research (CAR). The subjects of this study were the children of group B of PAUD Hubbul Ilmi, which consisted of 17 students consisting of 10 boys and 7 girls. This classroom action research was carried out in two cycles, each cycle having two meetings. Data Analysis Techniques used in this study were qualitative which were analyzed descriptively in the form of percentages and quantitatively obtained through observation and interviews. Based on the results of several stages of research, it shows that mosaic activities can improve children's fine motor development as evidenced by the success indicators achieved in the first cycle, the percentage value is 52% with the criteria for Developing According to Expectations (BSH) and in the second cycle the success indicator becomes 91.91. % with Very Good Development (BSB) criteria. This means that through mosaic activities, children's fine motor development can be improved at PAUD Hubbul Ilmi in Sukamakmur Village of Girimulya Sub-District of North Bengkulu Regency, as evidenced by the percentage of 91.91% in the second cycle in the Very Good Developing category (BSB).